"Look on the bright side": CEO optimism and firms' market valuation. Issue 3 (8th February 2021) - Alshorman, Salah; Shanahan, Martin
Abstract : Purpose: Previous research suggests that a CEO's attitude can impact a firm's performance. More particularly, there appears to be a link between the CEO's revealed level of optimism and firm's market value. The purpose of this paper is to measure the level of optimism revealed by Australian CEOs in their shareholder letters and compares this with their firms' current and future valuations. Design/methodology/approach: This study assesses the CEO's level of optimism using text analysis of the annual letters to shareholders in 180 Australian-based firms from 2010 to 2013. The market valuation of their companies over the same period is calculated using Tobin's Q, and the results compared with the level of CEO optimism. Findings: Comparing the level of revealed optimism with their firms' valuations over four years, CEO optimism is positively correlated, both currently and prospectively with firm valuation. Given the period under study immediately followed the global financial crisis (GFC), the results suggest CEO optimism may be an important factor in adding to firm's market resilience. Research limitations/implications: The study examines the link between revealed CEO optimism and firm valuation over a turbulent period of the business cycle. While the sample period follows the GFC, and Tobin's Q has some known deficiencies, the results imply that further research should be undertaken to examine the importance of CEOs tone and communicated attitudes on their firms' financial outcomes. Practical implications: The link between CEO optimism and the firm's valuation suggest that shareholders and boards should pay particular attention to the values, cognitions and psychological and demographic characteristics of top executives when selecting CEOs. In particular, the results suggest that given two otherwise similar CEOs the one whose record of communication is optimistic should be preferred over a similarly qualified but less sanguine individual. Originality/value: The paper represents the first study demonstrating the link between CEO's communicated optimism and Australian firms' valuations. The study uses three different measures of optimism to improve the robustness of its conclusions, and a comprehensive measure of firm value – Tobin's Q. It is the first to quantify the association between CEO optimism and firm value shortly after a period of financial upheaval (the GFC). The findings indicate that CEO optimism contributes significantly to firm value. The study also tests whether "excessive" optimism negatively impacts firm performance and conclude there is no evidence of this in the sample period. The study suggests that more research should be done to examine the contribution of positive business attitudes to periods of economic stress.